Tingkat Pengetahuan Penulisan Resep Pada Mahasiswa Tingkat Akhir Tahap Sarjana Program Studi Kedokteran Universitas Malahayati - Sri Maria Puji Lestari; Esteria Marhayuni; Dessy Hermawan; Mutiara Ghassani Pangestu (Universitas Malahayati, 2021)
ABSTRACT: KNOWLEDGE LEVEL OF RECEPTION WRITING AT END LEVEL BACHELOR STAGE BACHELOR OF MEDICAL STUDY PROGRAM, MALAHAYATI UNIVERSITY, 2020 Background: Prescription is the most important therapeutic transaction between doctor and patient in which a written order is attached about the drug to be used for the prevention of complications and the treatment of patient diagnosis directed by the doctor. Prescription writing is one of the materials studied by medical students, especially final year students because they have passed almost all clinical blocks. Objective: Determine the level of knowledge of prescription writing in the final year undergraduate students of the Malahayati University medical study program.Methodology: The type of research used in this research is descriptive quantitative. With a measuring instrument using a prescription writing questionnaire that has been tested for validity and reliability to the respondent. Result: Of the 190 respondents consisting of 63 men and 127 women who filled out the questionnaire, the knowledge level of prescription writing was obtained 96 respondents (50.5%) sufficient knowledge, 92 respondents (48.4%) good knowledge, and 2 respondents (1.1%) lack of knowledge. Conclusion: The majority of prescription writing knowledge of final year students of the Malahayati University medical study program has sufficient knowledge. With the topic of discussion, the majority of which were controlled by the respondents was the authority to write prescriptions and the less mastered was the abbreviation of prescription. Keywords: Knowledge Level, Prescription Writing INTISARI: TINGKAT PENGETAHUAN PENULISAN RESEP PADA MAHASISWA TINGKAT AKHIR TAHAP SARJANA PROGRAM STUDI KEDOKTERAN UNIVERSITAS MALAHAYATI TAHUN 2020 Latar Belakang: Resep merupakan sebuah transaksi teurapeutik terpenting antara dokter dengan pasien yang didalam nya terlampir perintah tertulis tentang obat yang akan digunakan untuk pencegahan komplikasi dan pengobatan diagnosis pasien yang diarahkan oleh dokter. Penulisan resep merupakan salah satu materi yang di pelajari mahasiswa kedokteran, terutama mahasiswa tingkat akhir karena telah melewati hampir seluruh blok klinis.Tujuan: Mengetahui tingkat pengetahuan penulisan resep pada mahasiswa tingkat akhir tahap sarjana program studi kedokteran Universitas Malahayati.Metodologi: Jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Dengan alat ukur menggunakan kuesioner penulisan resep yang telah diuji validitas dan realibilitasnya kepada responden.Hasil: Dari 190 responden yang terdiri dari 63 laki-laki dan 127 perempuan yang mengisi kuesioner tingkat pengetahuan penulisan resep didapatkan 96 responden (50,5%) pengetahuan cukup, 92 responden (48.4%) pengetahuan baik dan 2 responden (1,1%) pengetahuan kurang.Kesimpulan: Mayoritas pengetahuan penulisan resep mahasiswa tingkat akhir program studi kedokteran Universitas Malahayati memiliki pengetahuan cukup. Dengan topik bahasan yang mayoritas sangat dikuasai responden adalah wewenang menulis resep dan yang kurang dikuasai adalah singkatan peresepan. Kata Kunci : Tingkat Pengetahuan, Penulisan Resep